Intensified photocatalytic degradation of 2, 4–dicholorophenoxyacetic acid using size-controlled silver nanoparticles: effect of pre-synthesis extraction - Rohayu, Jusoh; N.S., Kamarudin; Nuramira Fateha, Sukor; Aishah, Abdul Jalil; Setiabudi, H. D. (Elsevier Ltd, 2020)
In this study, ultrafine silver (Ag) nanoparticles were synthesised in Orthosiphon stamineus (OS) extract via facile electrochemical method. Different pre–synthesis extraction methods, namely ultrasonic assisted extraction hydro–distillation (UAE–HD) and classical aqueous extraction (AE) were used and compared. UAE–HD attained the highest total phenolic compounds at 8563.90 mg/kg. The Ag nanoparticles prepared via pre–synthesis extraction of UAE–HD (AgUAE-HD) and classical AE (AgAE) gave ultrafine sizes of 2 nm and 15 nm, respectively. It was suggested from the characterisation results that the phenolic compounds present in the OS extract had a significant role in the capping and stabilisation of Ag nanoparticles. Moreover, it was also demonstrated that the size of the Ag nanoparticles could simply be altered by varying the amount of total phenolic content (TPC) using different pre–synthesis extraction methods prior to the synthesis of Ag. Next, the photocatalytic activity of the Ag nanoparticles was tested towards the degradation of 2, 4–dicholorophenoxyacetic acid (2,4–D) herbicide. The synthesised Ag nanoparticles also showed outstanding photocatalytic activity with maximum degradation efficiency of up to 99.78% at pH 3, 0.01 g L−1 of catalyst dosage and 10 mg L−1 of 2, 4-D concentration. High amount of TPC contributed to the low energy band–gap (Eg) of AgUAE-HD catalyst and significantly inhibited the electron-hole recombination as well as enhanced the photocatalytic activity. The figures of merit based on electric energy consumption (EEO) indicate that less energy was consumed during the degradation of 2,4–D in the presence of AgUAE-HD compared with other catalysts. Therefore, it could be concluded that AgUAE-HD is a promising material for high photocatalytic degradation efficiency of 2,4–D under optimal condition.